2016
DOI: 10.1002/nau.23159
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral spinal segmental contributions to tibial and pudendal neuromodulation of bladder overactivity in cats

Abstract: AIMS To determine the spinal segmental afferent contributions to tibial and pudendal inhibition of bladder overactivity. METHODS Intravesical infusion of 0.5% acetic acid was used to irritate the bladder and induce bladder overactivity in anesthetized cats. Tibial or pudendal nerve stimulation was used to suppress the bladder overactivity and increase bladder capacity during cystometry. L5-S3 dorsal roots ipsilateral to the stimulation were exposed by a laminectomy and transected sequentially during the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The dense hypertrophic megaloneurites extending from dorsal entry zone and LT through lamina along the lateral edge of the dorsal horn to the region of the sacral parasympathetic nucleus (SPN). The sacral DGC and the LCP receives terminations from the somatic and visceral afferents (Morgan et al, 1981;Thor et al, 1989;Al-Chaer et al, 1996;Bansal et al, 2017). Functionally, the sacral spinal cord is known to be associated with bowel bladder, and sexual dysfunction (Cohen et al, 1991;Ogiwara and Morota, 2014;Barbe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dense hypertrophic megaloneurites extending from dorsal entry zone and LT through lamina along the lateral edge of the dorsal horn to the region of the sacral parasympathetic nucleus (SPN). The sacral DGC and the LCP receives terminations from the somatic and visceral afferents (Morgan et al, 1981;Thor et al, 1989;Al-Chaer et al, 1996;Bansal et al, 2017). Functionally, the sacral spinal cord is known to be associated with bowel bladder, and sexual dysfunction (Cohen et al, 1991;Ogiwara and Morota, 2014;Barbe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The sacral spinal cord is more specifically related to the intestine, bladder and sexual dysfunction (Cohen et al, 1991;Ogiwara and Morota, 2014;Barbe et al, 2018). In the dorsal gray commissure (DGC) in the S1-S3 segments of the cat spinal cord, this region receives the terminals of visceral afferent fibers in the pelvic nerves and somatic afferent fibers for the pudendal nerves through the Lissauer's tract (LT) and its lateral-and medial-collateral projections (McKenna and Nadelhaft, 1986;Thor et al, 1989;Liu et al, 1998;Bansal et al, 2017). The retrograde transganglionic labeling of primary afferent fibers from the bladder (Wang et al, 1998), urethra (Vizzard et al, 1995) and external urethral sphincter (Nadelhaft and Vera, 1996), as well as from the penile nerve (McKenna and Nadelhaft, 1986) has indicated that DGC is a part of the reflex pathways that control the functions of the pelvic viscera (Palecek and Willis, 2003;Cruz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the CMG model, peripheral nerve stimulation to anesthetized animals prolonged the latency of urination, indicating an increased volume threshold of the micturition reflex (Su et al, ; Choudhary et al, ; Jiang et al, ; Kadow et al, ; Rogers et al, ; Bandari et al, ; Bansal et al, ; Fuller et al, ; Uy et al, ; Zhang et al, ). In the RMC model, peripheral nerve stimulation abolished periodic intravesical pressure changes, reflecting suppression of the micturition reflex at a volume that was previously supra‐threshold (Su et al, ; Kovacevic and Yoo, ; Su et al, ; Onda et al, ; Ren et al, ).…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%
“…In studies examining the effects of peripheral nerve activation by electrical stimulation on urinary bladder functions, stimulation is commonly applied to the tibial nerve, pudendal nerves, or the sacral nerves (Su et al, 2013a(Su et al, , 2013b(Su et al, , 2015Kovacevic and Yoo, 2015;Choudhary et al, 2016;Jiang et al, 2016;Kadow et al, 2016;Onda et al, 2016;Ren et al, 2016;Rogers et al, 2016;Bandari et al, 2017;Bansal et al, 2017;Fuller et al, 2017;Uy et al, 2017;Zhang et al, 2017). Hence, somatic afferents sending sensory inputs to spinal levels near pelvic nerve efferent outputs innervating the bladder are generally targeted for stimulation.…”
Section: Effects Of Somatic Electrical Stimulation On the Micturitionmentioning
confidence: 99%
See 1 more Smart Citation